PENERAPAN BALANCED SCORECARD SEBAGAI SISTEM PENGUKURAN KINERJA: (Studi Kasus Koperasi Simpan Pinjam CU Sondang Nauli) - Simorangkir, Benni; Saragih, Joana L. (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This study aims to determine the performance of the CU Sondang Nauli Savings and Loans Cooperative when measured by applying the Balanced Scorecard concept through four perspectives, namely: Financial perspective, Customer perspective, Internal business process perspective and Growth and learning perspective. The population in this study is the financial statements and member data of the Sondang Nauli CU Savings and Loan Cooperative, the samples in this study are financial statements, member data, and employee data of the 2022 CU Sondang Nauli Savings and Loan Cooperative. Data collection techniques in this study were carried out by interview, documentation and questionnaire techniques. The data analysis technique used in this study is a descriptive analysis technique. Based on the results of the study showed that the performance from a financial perspective of 33,57%, a customer perspective of 69,43%, an internal business process perspective of 93,68%, and a growth and learning perspective of 100%, the total performance of the CU Sondang Nauli Savings and Loans Cooperative is 74% included in the A or